Analysis of heat transport and thickness of bimetal composition layer between low-alloy steel and high-chromium white cast iron. (May 2015) - Zhu, Y. C.; Wei, Z. J.; Rong, S. F.; Li, X. Y.; Duan, X. L.
<x content-type="archive" xml:space="preserve">Abstract</x> Two-liquid bimetal casting technique was worthy of being widely used in wear-resistant materials. Research on the fusion mechanism at the bimetal composite layer can lay the theoretic foundation for the extension of the dissimilar ferroalloy composition material. Two-liquid bimetal between the low-alloy steel and high-chromium white cast was prepared by controlling the pouring temperature, and the composite layer microstructure and composition distribution were studied. In accordance with the detected results, two-liquid bimetal casting technique can be assured, and the various casting technique parameters have an obvious effect on the composite layer microstructure. To maintain the casting technique stability, the freezing time and element diffusion of the low-alloy steel were evaluated and analysed.